Response to LiPuma and DeMarco's Article on "Hastening Death" - Julia Zenz (SAGE Publishing, 2017)
The paper "Palliative care and patient autonomy: moving beyond prohibitions against hastening death" by LiPuma and DeMarco deals with an aspect of end of life care which is the source of considerable disagreement. It is important to emphasize that autonomy is not the unique feature for end of life care. There is always a medical and ethical commitment to care, i.e. beneficence and nonmaleficence. All of these aspects have to be taken into account when treating patients at the very end of life. There is considerable scientific proof indicating that most patients and families can experience a death in dignity when being cared for in palliative care or hospice units.